2014
DOI: 10.1373/clinchem.2014.222976
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatography High-Resolution TOF Analysis: Investigation of MSE for Broad-Spectrum Drug Screening

Abstract: MS(E) provides a unique way to incorporate fragment ion information without the need of precursor ion selection. A primary limitation of requiring a fragment ion for positive identification was that certain drug classes required high-energy collisions, which formed many fragment ions of low abundance that were not readily detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Results from metabolite profiling studies using MS E or SWATH suggested that a combination of the QTOF and data-independent global fragment acquisition provides a powerful approach to high-throughput screening of drug metabolites in biological matrices. In addition, MS E and SWATH provide a useful means of structural confirmation when a QTOF is employed for quantitative analysis of a large number of analytes using accurate mass full MS scan data (Chindarkar et al, 2014;Siegel et al, 2014).…”
Section: Hrms-based Data Acquisition Technology For Drug Metabolite Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from metabolite profiling studies using MS E or SWATH suggested that a combination of the QTOF and data-independent global fragment acquisition provides a powerful approach to high-throughput screening of drug metabolites in biological matrices. In addition, MS E and SWATH provide a useful means of structural confirmation when a QTOF is employed for quantitative analysis of a large number of analytes using accurate mass full MS scan data (Chindarkar et al, 2014;Siegel et al, 2014).…”
Section: Hrms-based Data Acquisition Technology For Drug Metabolite Dmentioning
confidence: 99%
“…On the other hand, MS E or SWATH would be useful in the structural confirmation of over 50 components when they are subjected to quantitative analysis or screening using full scan MS on an HRMS instrument (Chindarkar et al, 2014). Another new HRMSbased strategy is the use of HRMS in profiling, identification, and quantitative estimation of plasma metabolites in humans in early clinical studies to address concerns of metabolite safety testing (Aubry et al, 2014;Ma et al, 2010;Zhu et al, 2009a).…”
Section: Hrms-based Analytical Strategy For Drug Metabolite Detectionmentioning
confidence: 99%
“…In contrast, data-independent acquisition approaches, such as All Ion Fragmentation (Orbitrap), MS E (TOF-MS), and SWATH (TripleTOF), apply collision energy without selection of a precursor mass. For example, MS E alternates between low and high collision energies and the resulting spectra are screened against specified molecular databases [109,110]. A similar approach is Sequential Windowed Acquisition of All Theoretical Fragment Ion Mass Spectra, or SWATH, which dissociates compounds in selected isolation width windows (e.g., 21 Da) rather than the entire mass range to limit the number of potential interfering compounds [111].…”
Section: Tandem Mass Spectrometrymentioning
confidence: 99%
“…To address the fourth issue of multiplexed SRM/MRM, methods for using retention time standards have been developed, which allow the transfer of retention times from one chromatography platform to be transferred to another [63,64]. However, there is a concern with the number of targets to analyze in a single liquid chromatography–mass spectrometry analysis, and data independent acquisition approach such as energy dependent fragmentation and sequential window acquisition of all theoretical fragment-ion spectra techniques provides a solution [65,66]. To address the last issue, the low-abundant targets were enriched using upfront target enrichment followed by SRM analysis [67,68].…”
Section: Five-year Viewmentioning
confidence: 99%